Pengembangan Aplikasi Manajemen Stok Barang Berbasis Web untuk Meningkatkan Efisiensi Operasional di Toko Bangunan Sinar Kudus Nabire - Fernando Ewak; Ester Ayuk Pusvita (Jurnal Teknologi dan Informatika, 2025)
Inventory management is a critical aspect of retail operations, including at Sinar Kudus Nabire Building Materials Store. The current manual system is prone to recording errors, data loss, and slow stock updates, leading to operational inefficiency and risks of overstock or stock shortages. This study aims to develop a web-based inventory management application using the Agile method to improve efficiency and accuracy in stock management. The application is designed with features for real-time stock recording, searching, and updating, as well as a login system for security. The results show that the application accelerates the process of searching and updating stock data, reduces the risk of overstock and stock shortages, and facilitates decision-making related to inventory management. Academically, this research contributes to the literature on the development of web-based inventory management applications, particularly for building material stores. Practically, the application helps improve operational efficiency and stock data accuracy at Sinar Kudus Nabire Building Materials Store. This study is limited to developing a basic inventory management application and does not cover other operational aspects such as finance or marketing.